1991
DOI: 10.1161/01.str.22.11.1409
|View full text |Cite
|
Sign up to set email alerts
|

Clentiazem protects against chronic cerebral vasospasm in rabbit basilar artery.

Abstract: Background and Purpose: Experiments were carried out in rabbits to determine whether clentiazem (8-chlorodiltiazem), a cerebrovascular-selective calcium channel blocker, administered 24 hours before subarachnoid hemorrhage influenced the subsequent cerebral vasospasm.Methods: Subarachnoid hemorrhage was induced by multiple injections of blood into the prepontine cisterns of 35 male New Zealand White rabbits, and clentiazem (5 nig/kg) was administered 4 times daily until sacrifice. Cerebral artery diameter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…3, Panel C1). 33,[48][49][50][51][52][53][54][55][56][57][58] The double injection method generates a slightly more delayed onset of vasospasm, with a peak onset between day 4 and day 6 after initial hemorrhage (Fig. 3, Panel C2).…”
Section: Resultsmentioning
confidence: 99%
“…3, Panel C1). 33,[48][49][50][51][52][53][54][55][56][57][58] The double injection method generates a slightly more delayed onset of vasospasm, with a peak onset between day 4 and day 6 after initial hemorrhage (Fig. 3, Panel C2).…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximal contraction to KC1 was not changed [12,15] after SAH. On the other hand, it was reported that the contractions to 5-HT, NE, and KC1 were suppressed in rabbit SAH, using the same method, due to increased wall stiffness and transient spontaneous changes in wall force [16]. In cat SAH, induced by the same method, the rings of posterior communicating arteries displayed a supersensitivity to 5-HT and NE, 3 days after SAH.…”
Section: Cerebrovascular Contraction After Sahmentioning
confidence: 87%
“…In rabbit SAH, the vasodilation to ACh was not significantly reduced and that to ATP was significantly attenuated in the rings of basilar arteries contracted with 5-HT, 2 days after SAH produced by a single blood injection into the major cistern [12], while both ACh-and ATPinduced relaxation was suppressed in the same arteries 4 days after SAH by two successive blood injections [37]. The relaxation to ACh was significantly depressed after SAH in the same arterial rings pretreated with histamine [16]. In dog SAH produced by the doublehemorrhage method, the endothelium-dependent relaxation to arginine vasopressin was abolished and that to thrombin was significantly reduced, and the endothelium-independent relaxation to papaverine was preserved in the rings of basilar arteries contracted with uridine triphosphate, 8 days after SAH [25].…”
Section: Cerebrovascular Relaxation @Er Sahmentioning
confidence: 93%
“…This model is considered to be relatively well developed and is broadly accepted. Some studies reported matrix remodeling of cerebral arteries in different species following experimental SAH and proposed that a main cause of vasospasm is the increased rigidity of the artery wall [38,39,40,41]. However, carotid artery blood flow measurements in rats revealed no reduction in flow after 3 days, which would be expected from a state of vasospasm of the brain vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Vorkapic et al [39] found increased artery wall stiffness of basilar arteries in the rabbit double hemorrhage model. Kim et al [38] studied mechanical properties of basilar arteries in dogs induced by two cisternal injections of autologous blood.…”
Section: Discussionmentioning
confidence: 99%